2018
DOI: 10.3390/jcs2030054
|View full text |Cite
|
Sign up to set email alerts
|

The Magneto-Mechanical Behavior of Active Components in Iron-Elastomer Composite

Abstract: Abstract:The magneto-rheological effects in iron-elastomer composites (IEC) were investigated by simulation, surface topography, and 3D representation. The simulated behavior of magneto-rheological elastomeric composites in the presence of an external magnetic field was determined and the influence of magnetic intensity on the isotropic distribution of iron filler particles in IECs was investigated. The magnetic intensity distribution was analyzed from the edge of the surface towards the center of the IEC. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 26 publications
1
35
0
Order By: Relevance
“…The mold was fixed to the cover with the help of bolts (5). The tight closure of the mold by covers (1) was ensured by properly tensioned aluminum alloy bolts (2). During sample curing, the mold was subjected to a magnetic field along their axles.…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The mold was fixed to the cover with the help of bolts (5). The tight closure of the mold by covers (1) was ensured by properly tensioned aluminum alloy bolts (2). During sample curing, the mold was subjected to a magnetic field along their axles.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Magnetorheological elastomers (MRE) are a group of composite materials, the mechanical properties of which change under the influence of an applied magnetic field [1,2]. This change occurs in a time range counting up to several milliseconds, and is fully reversible [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The internal defects include fiber pull out, misalignment of the fiber, cracks, and damage to the matrix. In this work, we addressed the detailed statistical characterization of geometrical defects in the impacted fabric reinforced composite with 3D images captured by µCT to visualize the interior structural details with high resolution on a scale of interest for damage evaluation of the composite [21,22]. The relationships between the damaged area/volume and impact energies were established, and the composite was characterized, not only investigating the volume of the damaged area, but also the internal damage area including the internal structure and fiber breakage on the various layers of the composite structure.…”
Section: Introductionmentioning
confidence: 99%
“…The interest in this type of materials is constantly increasing due to the inexhaustible possibilities of their applications. In addition, compared to the well-known magnetorheological fluids [MRFs] there is still a lot to improve in terms of both material and processing issues [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the survey of the subject literature [1,2,4,5] it can be concluded that it is easier and cheaper to manufacture isotropic than anisotropic elastomers. The mechanical properties of the former offer prospects of wide industrial application.…”
Section: Introductionmentioning
confidence: 99%